(untitled) (Fiep Bulletin - online, 2013)
This article aims to characterize the psychological profile on performance (PPP) of athletes from the swimming Club Botafogo Futebol e Regatas. According to Feijó (1998) psychological factors influence and are influenced in physical activity in which athletes are subjected. The PPP developed by Loehr (1982) identifies eight variables in psychological performance that are dependent variables in the study. Composed of 42 questions answered on a Likert scale of 5 points (1 - almost always - 2 - Often 3 - Sometimes 4 - Rarely 5 - Almost Never). The focus of this study are the characteristics of personality: self-confidence, control of negativism, attentional focus, mental imagery, motivation, positive thoughts, attitudes and control of mental strength, the sum of them all. It was concluded that athletes have to swim a drop in performance due to psychological factors.